Investigation of Multiwavelength Laser Performance based on Temperature Variation of PMF and different SOAs - Sulaiman, Abdul Hadi; Abdullah, Fairuz; Ismail, Aiman; Jamaludin, Md Zaini; Md Yusoff, Nelidya; Mahdi, Mohd Adzir (International Journal of Integrated Engineering, 2018)
We demonstrated a multiwavelength performance based on bidirectional Lyot filter at different temperature of polarization maintaining fiber (PMF) and semiconductor optical amplifiers (SOAs). The multiwavelength fiber laser (MWFL) based on bidirectional Lyot filter is not investigated thoroughly on its channel spacing tunability due to birefringence change. A channel spacing of this MWFL is tunable due to birefringence change of the PMF. The birefringence value of is changed by heating the PMF, that leads to narrower channel spacing. From the experimental data, the temperature coefficient based on PMF length of 53.2 m and 10.6 m is 0.49 ×10-3 nm/°C and 1.35 ×10-3 nm/°C, respectively, thus shorter PMF is more sensitive to temperature. We also investigated the multiwavelength performance at different SOAs. When the SOA from Qphotonics is changed to the SOA from Alphion, the extinction ratio is reduced from 15 dB to 8 dB. In terms of flatness value, the Qhotonics’s SOA has a flatter multiwavelength spectrum with only 1 dB of peak power difference from 1538 nm until 1541 nm as compared to 2.5 dB when using Alphion’s SOA.